Colour, citizenship and constitutionalism : an oral history of political identity among middle-class coloured people with special reference to the formation of the Coloured Advisory Council in 1943 and the removal of the male franchise in 1956 - Villa-Vicencio, Heidi (Department of Historical Studies, 2016)
Bibliography: pages 173-186.